2021
DOI: 10.1186/s12885-021-09040-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of AKR1 family in tamoxifen resistant invasive lobular breast cancer based on data mining

Abstract: Background Tamoxifen (TAM) resistance to invasive lobular cell carcinoma is a challenge for breast cancer treatment. This study explored the role of Aldo-keto reductase family 1 (AKR1) family in tamoxifen-resistant aggressive lobular breast cancer based on data mining. Methods TAM-resistant invasive lobular breast cancer gene chip was downloaded from the Gene Expression Omnibus (GEO) database (accession-numbered as GSE96670). The online analytical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…ERBB4 was downregulated while FN1 was upregulated in TAM-R cells. These findings are supported by previous studies that demonstrated the downregulation of ERBB4 ( 61 ), and the upregulation of FN1 in TAM resistance ( 62 64 ). Significant upregulation of VIM, NOTCH1, HES1 , and TP53 in was observed in TAM-R MCF-7 cells, indicating increased Notch signaling, epithelial to mesenchymal transition, and inhibition of cell cycle in TAM-R cells.…”
Section: Discussionsupporting
confidence: 89%
“…ERBB4 was downregulated while FN1 was upregulated in TAM-R cells. These findings are supported by previous studies that demonstrated the downregulation of ERBB4 ( 61 ), and the upregulation of FN1 in TAM resistance ( 62 64 ). Significant upregulation of VIM, NOTCH1, HES1 , and TP53 in was observed in TAM-R MCF-7 cells, indicating increased Notch signaling, epithelial to mesenchymal transition, and inhibition of cell cycle in TAM-R cells.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, Penning TM et al (2021) noted that these enzymes are involved in the modulation of carcinogen metabolism [35][36][37]. These studies have argued that aldo-keto reductase family 1 members (AKR1s) represent important emerging drug targets that could aid in the development of drugs for the treatment of hormone-dependent forms of cancer such as prostate, hepatocellular, colorectal, breast, and endometrial cancers as well as other diseases [10,14,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…Kamps R. et al claimed that gene expression-based diagnosis, as a new detection method, has diverse application potential in tumour identi cation, tumour monitoring, treatment plan optimization, and improving patient prognosis [12]. Previous studies have established that the expression pro les of AKR1s are an essential component in tumour identi cation and gene expression-based diagnosis [13,14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of 5Red3 to DHT synthesis and the clinical significance of 5Red3 in breast cancer are largely unclear. However, a recent database analysis showed that overexpression of 5Red3 correlates with lymph node metastasis and shorter overall survival of breast cancer patients (Zhang et al 2021).…”
Section: Intratumoral Synthesis and Metabolism Of Androgensmentioning
confidence: 99%